(untitled) (Tanzania Journal for Population studies and Development, 2019)
This study assesses the production trend of two irrigation schemes in Bunda district, namely Maliwanda and Namhula. It employs quantitative and qualitative research designs. Data was collected through questionnaires, interviews, observation, and documentary review. The findings indicate a positive trend in paddy production of the two schemes. The findings further reveal that after the application of irrigated agriculture, paddy yield increased from less than 2 tons per hectare to over 5 tons per hectare. The high yield was attributed not only to irrigation, but also to improved knowledge on rice production and the use of improved seeds that are highly productive and adaptive to local conditions. We recommend that to achieve sustainability of the two schemes, the current water association should be strengthened, annual fees be increased, and human activities around the schemes be restricted to avoid silting of the dams.